PENGARUH MODAL INTELEKTUAL TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN YANG TERGABUNG DALAM SAHAM LQ45 - Astuti, Neni; Fajri, Aminul (PERMANA, 2014)
The purpose of this study is to examine and analyze empirically the influence ofintellectual capital (VAIC) on financial performance which proxied by return on equity ratio (ROE). Samples were financial statements of the companies belonging to the LQ45 stocks in 2010-2013. It can be concluded that the VACA and STVA effect on financial performance (ROE).This study proved that the intellectual capital have an important role for thecreation of financial performance and high market value. Therefore, managers should improve the efficiency of physical capital, the efficiency of the employees management, organizational management and efficiency of the company to improve its financial performance and market value. In the selection of the investment, the investor can use the value of the three elements of intellectual capital to choose which company has the potential to produce good financial performance and high market value.Key Words : intellectual capital, VAIC, VACA, VAHU, STVA, financial performance (ROE)